2016
DOI: 10.1158/1078-0432.ccr-16-0015
|View full text |Cite
|
Sign up to set email alerts
|

Germline Analysis from Tumor–Germline Sequencing Dyads to Identify Clinically Actionable Secondary Findings

Abstract: PURPOSE To evaluate germline variants in hereditary cancer susceptibility genes among unselected cancer patients undergoing tumor-germline sequencing. EXPERIMENTAL DESIGN Germline sequence data from 439 individuals undergoing tumor-germline dyad sequencing through the LCCC1108/UNCseq™ (NCT01457196) study were analyzed for genetic variants in 36 hereditary cancer susceptibility genes. These variants were analyzed as an exploratory research study to determine if pathogenic variants exist within the germline of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 43 publications
4
62
0
Order By: Relevance
“…This resulted in "false somatic" calls reported as tier 3 or higher in 4 of 91 (4.4%) of patient samples. This finding is in keeping with the rate of significant occult germline variants found in cancer patients undergoing paired tumor-normal sequencing at other institutions (45).…”
Section: Discussionsupporting
confidence: 87%
“…This resulted in "false somatic" calls reported as tier 3 or higher in 4 of 91 (4.4%) of patient samples. This finding is in keeping with the rate of significant occult germline variants found in cancer patients undergoing paired tumor-normal sequencing at other institutions (45).…”
Section: Discussionsupporting
confidence: 87%
“…To address this question, multiple groups have performed retrospective studies of patients undergoing tumor-normal sequencing. In adult patients, the range of individuals with cancer who harbor an actionable pathogenic germline variant ranged from 3% to 12.6% depending on the population and genes studied [1][2][3][4]. In the pediatric population, pathogenic germline variants have been identified in the context of tumor-normal sequencing in 8.5-10% of children and adolescents with cancer [5][6][7].…”
mentioning
confidence: 99%
“…A study of targeted exome analysis of 202 genes, which included 18 actionable genes listed by ACMG and PALB2 , detected likely pathogenic variants in 43 of 1000 patients enrolled in the study . Another survey tumor‐germline paired sequencing identified germline variants suspected for hereditary tumor predisposition in 19 of 439 (4.3%) cancer patients . Recently, a study reported that 182 (17.5%) of 1040 patients with advanced cancer carried clinically actionable inherited mutations detected by tumor‐normal pair sequencing, and that 97, 52, and 33 of the 182 were identified in high‐, moderate‐, and low‐penetrance genes, respectively …”
Section: Incidental/secondary Findings In Ngs Panel Tests For Somaticmentioning
confidence: 99%